Advanced Sliding Mode Control with Disturbance Rejection Techniques for Multi-DOF Robotic Systems - Basal, Mohamed Abdelhakim (Universitas Muhammadiyah Yogyakarta, 2025)
For the control of complex and non-linear systems such as robotic arms, especially in sensitive systems such as medical applications and chemical industries, it becomes necessary to improve the performance considering the balance between fast response and smooth, vibration-free, in addition to overcoming disturbances and model uncertainty. These and other reasons may be the reason for the failure of some linear and classical control systems. This research presents a hybrid control system that combines sliding mode control (SMC) with an active disturbance rejection controller (ADRC) for a three-degree-of-freedom (3-DOF) robotic arm. The research contributes to developing a robust control system that reduces the vibrations caused by the classical SMC and utilizes its advantages to achieve smooth, fast, high dynamic response. The proposed method combines the benefits of SMC stiffness for regulating the angular velocities and ADRC in disturbance compensation to regulate the angular positions, ensuring smooth and accurate control despite its relative complexity. The simulation results show that the classical SMC methodology provides superior performance compared to the traditional PIDC in terms of low settling time, but suffers from higher overshoot and large vibrations that sometimes cause a large value of tracking error. In contrast, the proposed control methodology contributes to the improvement of the robotic arm performance, achieving higher tracking accuracy, tracking error minimization, very low settling time, and clear vibration cancellation in both the output signals and the applied control signals. The proposed system has clear advantages, so it can provide a promising solution for robotic arms, particularly in industries demanding high performance, fast tracking and minimal vibrations.